A Case Report of Focal Epithelial Hyperplasia (Heck’s disease) with PCR Detection of Human Papillomavirus - Ozden, Bora (Springer-Verlag, 2011)
Focal epithelial hyperplasia or Heck’s disease, is a rare viral infection of the oral mucosa caused by human papillomavirus. The frequency of this disease varies widely from one geographic region to another. In Caucasians there have been only few cases reported. This paper reports a case of focal epithelial hyperplasia and demonstrates the association with HPV subtype 32 through polymerase chain reaction (PCR) and sequencing of PCR products. A 7-year-old Caucasian girl was admitted to our clinic for investigation of multiple oral mucosal lesions in the mouth. Lesion was excised under local anesthesia without any complication. The lesion was diagnosed as focal epithelial hyperplasia according to both clinical and histopathological features. Dental staff should be aware of these kind of lesions and histopathological examination together with a careful clinical observation should be carried out for a definitive diagnosis.